2017
DOI: 10.1007/s10620-017-4716-6
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Predictors of Vaccinations Among Inflammatory Bowel Disease Patients Receiving Anti-Tumor Necrosis Factor Agents

Abstract: The rates of immunizations for IBD patients receiving anti-TNF treatment were lower than recommended. Structured reminders for vaccinations and education for both patients and providers (older physicians in particular) may prove beneficial in improving immunization rates among immunocompromised IBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…However, vaccination rates for these preventable diseases continue to be suboptimal in the face of a decade of research proving that IBD patients are at an increased risk of vaccine-preventable infections [96]. Prior data have shown that recommendations from physicians are the most important factor for receiving preventative health services such as vaccination and screening for cancer [97].…”
Section: Discussionmentioning
confidence: 99%
“…However, vaccination rates for these preventable diseases continue to be suboptimal in the face of a decade of research proving that IBD patients are at an increased risk of vaccine-preventable infections [96]. Prior data have shown that recommendations from physicians are the most important factor for receiving preventative health services such as vaccination and screening for cancer [97].…”
Section: Discussionmentioning
confidence: 99%
“… 8 Small studies have suggested that the presence of any comorbidity may increase vaccination uptake, 5 but others reported no association. 9 …”
mentioning
confidence: 99%
“…Nevertheless, as effective as biologics are in achieving and maintaining clinical and histologic remission as well as improving patients' quality-of-life, their use places recipients at a higher risk of infections. In this respect, the paper by Dr. Pham and colleagues [3] published in current issue of Digestive Diseases and Sciences yet again highlights an important issue of precautionary practices in the IBD population, examining the rates and predictors of vaccinations among IBD patients initiated on infliximab and adalimumab therapy in an integrated West Coast healthcare system.…”
mentioning
confidence: 99%